YOUNG LECTURERS URGED TO ENGAGE WITH THE COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Academic staff, especially young academics were urged to become involved in community engagement programmes to boost the university’s efforts to enhance the process of knowledge transfer to members of the community who require their knowledge and expertise.